Intellectual Property and Clean Energy The Paris Agreement and Climate Justice (Springer Singapore, 2018)
This collection considers the future of climate innovation after the Paris Agreement. It analyses the debate over intellectual property and climate change in a range of forums - including the climate talks, the World Trade Organization, and the World Intellectual Property Organization, as well as multilateral institutions dealing with food, health, and biodiversity. The book investigates the critical role patent law plays in providing incentives for renewable energy and access to critical inventions for the greater public good, as well as plant breeders' rights and their impact upon food security and climate change. Also considered is how access to genetic resources raises questions about biodiversity and climate change. This collection also explores the significant impact of trademark law in terms of green trademarks, eco labels, and greenwashing. The key role played by copyright law in respect of access to environmental information is also considered. The book also looks at deadlocks in the debate over intellectual property and climate change, and provides theoretical, policy, and practical solutions to overcome such impasses.